Evaluating and Screening of Agro-Physiological Indices for Salinity Stress Tolerance in Wheat at the Seedling Stage - Tao, Rongrong; Ding, Jinfeng; Li, Chunyan; Zhu, Xinkai; Guo, Wenshan; Zhu, Min (Frontiers in Plant Science, 2021)
Soil salinity is a worldwide issue that affects wheat production. A comprehensive understanding of salt-tolerance mechanisms and the selection of reliable screening indices are crucial for breeding salt-tolerant wheat cultivars. In this study, 30 wheat genotypes (obtained from a rapid selection of 96 original varieties) were chosen to investigate the existing screening methods and clarify the salinity tolerance mechanisms in wheat. Ten-day-old seedlings were treated with 150 mM NaCl. Eighteen agronomic and physiological parameters were measured. The results indicated that the effects of salinity on the agronomic and physiological traits were significant. Salinity stress significantly decreased K+ content and K+/Na+ ratio in the whole plant, while the leaf K+/Na+ ratio was the strongest determinant of salinity tolerance and had a significantly positive correlation with salt tolerance. In contrast, salinity stress significantly increased Na+ concentration and relative gene expression (TaHKT1;5, TaSOS1, TaAKT1-like). The Na+ transporter gene (TaHKT1;5) showed a significantly greater increase in expression than the K+ transporter gene (TaAKT1-like). We concluded that Na+ exclusion rather than K+ retention contributed to an optimal leaf K+/Na+ ratio. Furthermore, the present exploration revealed that, under salt stress, tolerant accessions had higher shoot water content, shoot dry weight and lower stomatal density, leaf sap osmolality, and a significantly negative correlation was observed between salt tolerance and stomatal density. This indicated that changes in stomata density may represent a fundamental mechanism by which a plant may optimize water productivity and maintain growth under saline conditions. Taken together, the leaf K+/Na+ ratio and stomatal density can be used as reliable screening indices for salt tolerance in wheat at the seedling stage.